Avaliação da eficiência na atenção básica à saúde nos municípios do estado do Ceará - Josué, Maria do Socorro (2015)
Improve process efficiency and application of resources is essential for health systems in the world. Perform diagnostics that help decision making in a complex ambience such as healthcare, is a hard challenge. This study evaluates the provision of services in Primary Health Care to population who live in cities in Ceará, in 2012, building a ranking efficiencies and explaining them by the influences of infrastructure and socio-economic variables of the cities, that get out of control of local health managers. The study was based on information found in public databases DATASUS and indexes of relative efficiencies were generated using the non-parametric model of Data Envelopment Analysis (DEA), oriented to products. We used several indicators of monitoring and evaluation of the Pacto pela Saúde (Health Pact), from the biennium 2013-2015, signed by the three federal entities. The results indicate percentages between 22 and 56% of efficient cities. The analysis realize that, on average , cities with a population with up to 20.000 inhabitants present greater efficiency in Primary Health Care, that there is no direct relationship between per capita spending and efficiency and that GDP per capita has zero action in relation to efficiency. The eight cities with a population in excess of 100,000 were left off the efficient frontier. Only four cities had efficiency ratio below 50%, especially Fortaleza, capital of Ceará, which had a 35% efficiency rating. Regression analyzes indicated, on the one hand, that the efficiencies are directly related to higher proportions of rural population attended by Primary Health Care. On the other hand, there is an inverse relationship with the higher proportions of households with sewer system and households with masonry walls and similar. The results obtained with this study may be used by city managers, to planning and decision making about resource use and production activities and services in Primary Health Care.